STEREOLOGY AND SOME STRUCTURAL CORRELATES OF RETINAL AND PHOTORECEPTOR CELL FUNCTION - Mayhew, Terry M (Image Analysis and Stereology, 2011)
The retina is the part of the eye which detects light, transduces it into nerve impulses and plays a significant role in visual perception. Sensitivity to light is multi-factorial and depends on the properties of photopigment molecules, their synthesis and incorporation into photoreceptor membranes and the neural circuitry between photoreceptor cells, bipolar neurons and ganglion neurons. In addition, it depends on structural factors such as the absolute and relative numbers of different types of photoreceptor neurons, their subcellular morphology, their distribution across the retina and the physical dimensions (especially surface areas) and spatial arrangements of their photoreceptor membranes. At the molecular level, these membranes harbour photosensitive pigment molecules comprising transmembrane glycoproteins (opsins, which vary between photoreceptor cells) and a non-protein chromophore. Phototransduction involves a conformational change in the chromophore and activation of an opsin. A transducer G protein, transducin, lowers levels of cGMP and triggers changes in membrane ion permeability including the closure of Na+ channels. This causes the plasmalemma to become less depolarized and the relative hyperpolarization stimulates ganglion cells whose axons form the optic nerve. Phosducin is a light-regulated phosphoprotein located in inner and outer segments of rod photoreceptor cells. It modulates phototransduction by binding to beta and gamma subunits of transducin. This review briefly illustrates ways in which stereology can contribute to our understanding of these processes by providing quantitative data on photoreceptor number, disk membrane surface area and the subcellular immunolocalisation of key molecules.